Methode zur Bewertung der Zuverlässigkeit der elektrischen Energieversorgung in der automobilen Vorentwicklung - Mürken, Michael (Karlsruher Schriftenreihe Fahrzeugsystemtechnik, 2023)
With the introduction of highly automated assistance systems in passenger cars, the requirements for the reliability of the electrical power supply increase significantly. In this thesis, a method for evaluating the reliability of the electrical power supply in automotive pre-development is presented and applied. As a result, it could be shown that the classical electrical power supply is not suitable for supplying highly automated assistance systems.